Dutch Cookbooks Printed in the 16th and 17th Centuries - Meijer, Berthe (Petits Propos Culinaires, 2024)
The author gave a very interesting talk on this subject at the first Oxford Symposium in 1980. Very little information in English (or indeed in Dutch-see the end of the article) is available on this subject. So we asked Berthe Meijer to turn her speaking notes into an article, which she has kindly done. For those who are unfamiliar with current Dutch writing on food and food history, we should introduce her as one of the foremost practitioners in this field. The reports which she published in the Netherlands on the Oxford Symposia were the fullest to appear anywhere.